1998
DOI: 10.1677/joe.0.1560213
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian function in ewes made hypogonadal with GnRH antagonist and stimulated with FSH in the presence or absence of low amplitude LH pulses

Abstract: This study examined the effect of LH pulses, of similar amplitude and frequency to those found in the luteal phase, on the pattern of hormone secretion and follicle development in GnRH antagonist-suppressed ewes stimulated with exogenous FSH. This experiment was conducted on ewes with ovarian autotransplants in a continuous study. Follicle development was suppressed in 18 ewes by 3 weeks of GnRH antagonist treatment (50 µg/kg per 4 days s.c.), and was then stimulated by infusion of ovine (o)FSH (5 µg NIADDK-oF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…The follicular response induced by a single injection of the chimeric protein also reflects the long-lived nature of the single-chain gonadotropin analogs in sheep (9). Lemke et al (27) demonstrated that the single-chain analogs of the human gonadotropins were also active in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The follicular response induced by a single injection of the chimeric protein also reflects the long-lived nature of the single-chain gonadotropin analogs in sheep (9). Lemke et al (27) demonstrated that the single-chain analogs of the human gonadotropins were also active in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…As in other species (Richards 1980), E 2 synthesis in sheep requires input from both the thecal and granulosa cells (Baird 1977, 1983, England et al 1981. The essential role of the gonadotropins in ovarian function is illustrated by the arrest offollicle development and E 2 synthesis in mature ewes made deficient in the gonadotropins by hypophysectomy (Draincourt et al 1987), hypothalamopituitary disconnection (Hudson et al 1999), immunoneutralization of endogenous GnRH (McNeilly et al 1986), or administration of long-lived GnRH agonists (McNeilly & Fraser 1987) or antagonists (Campbell et al 1998). Moreover, follicle development and E 2 synthesis are reinstated in gonadotropin-deficient sheep by administration of LH and FSH (Campbell et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In sheep, ovarian weight is dramatically reduced, and follicle maturation and ovulation are blocked after the removal of gonadotropin support by hypothalamo-pituitary disconnection (Hudson et al 1999), hypophysectomy (Dufour et al 1979), immunoneutralization of gonadotrophin-releasing hormone (GnRH; Sakurai et al 1992), or administration of GnRH antagonists (Campbell et al 1998). These anti-gonadal responses are reversed by administration of supplemental gonadotropic stimuli (Fry et al 1988, Campbell et al 1998. The magnitude of the ovarian response increases with progressive increase in the level of exogenous gonadotropin administration and high levels of supplemental FSH induce a superovulatory response (McGowan et al 1985, Hudson et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…10 mm in diameter in the absence or presence of LH. The ability of FSH alone to promote follicular growth to preovulatory sizes has been demonstrated in sheep that were treated with a GnRH antagonist and exogenous FSH for at least 3 days (Campbell et al 1998. However, in studies conducted with GnRHa (Gong et al 1996, Garverick et al 2002 or GnRH-immunized heifers (Crowe et al 2001), treatment with exogenous FSH for 48 h did not result in follicle growth greater than 9 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%